Techno-Enviro-Economic Approach for Electrification of Rural and Shrimp Farming Regional Development of An Isolated Island in Indonesia by Utilizing Hybrid Renewable Energy Systems - Wijaya, Fiqih Akbar; Indianto, Mohammad Akita (Journal of Materials Exploration and Findings, 2025)
One of the challenges in developing and archipelagic countries such as Indonesia is maintaining energy demand in rural and isolated areas due to difficulties in electrical distribution. For instance, in areas like Bawean Island, no additional electricity capacity has been introduced in the past year, leading to an unmet potential customer demand. One of the possible options is by utilizing Hybrid Renewable Energy Systems (HRES) that are integrated with existing fossil fuel-based energy systems to support the growing energy demand in the remote island. A case study in Bawean Island is conducted with the projected energy demand covers the energy consumption for rural electricity and development for business and industry, in this case shrimp pond agriculture industry. The energy demand is projected until 2035 with increase needs for industry is an average of 5% to 7%. A techno-enviro-economic analysis utilizing Homer Pro software is conducted to determine the optimal configuration of energy systems. Three scenarios with different configurations of solar PV, wind turbines and existing fossil fuel-based grids are simulated. In scenarios I, II, and III, annual CO2 emissions are 33.6%, 37.16%, and 47.3% lower than in the Grid system. The technical and economic research shows that Scenario I, with a 10.5 MW grid configuration and 17.25 MW photovoltaic capacity system on 26.91 hectares of land, is the optimal implementation priority. Scenario I has the lowest LCOE (0,1580 $/kWh), highest NPV ($7.910.714), and shortest payback period (9 years 7 months). This indicates the potential to enhance productive sectors, particularly shrimp ponds.